PRICE VOLATILITY OF SHALLOT AND GARLIC AND EFFECT ON INFLATION IN EAST JAVA - Ayu Wulandari Priyambodoi; Dyanasari Dyanasari (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2022)
This study aims to analyze changes in prices and volatility of food commodities and their effect on inflation in East Java. The food commodities in this study were shallots and garlic. The purpose of this study is to identify the existence of price volatility of shallots and garlic, this study uses the ARCH / GARCH model. Then, this study uses further analysis using the ECM (Error Correction Model) model to determine the effect of price changes and the volatility of shallots and garlic on inflation in East Java. The ARCH-LM test results show that price volatility occurs in changes in garlic prices. Then the estimation results of the ECM model show that changes in garlic prices, real exchange rates and real interest rates have a significant positive effect on inflation in East Java. In this study, the price of shallots has no significant effect on inflation in East Java